Different Impact of Critic’s and Fellow Customer’s Score at Online Review Aggregator on Customer Purchase Intention in Motion Picture Industry - Laheba, T.R. (International Journal of Industrial Engineering and Engineering Management, 2019)
The Motion picture industry is somehow a unique industry when compared to other industries. Ticket prices for all films are the same, because of that price is not the main variable in decision making for watching a film. A review can become one of the most powerful variable when choosing which film to watch by the customer. Other than that, different from other industries and products, reviews that come in the form of narrative and detailed expositions tend to be avoided by customers because it will ruin the satisfaction of watching films activity due to leakage of information from the film plot and storyline. One that can be an aid for film customer is online review aggregator’s score that accumulated from a bunch of scores that are given from either critics or fellow customer and it made online review aggregator viewed as a more objective reviewer. This study aims to find whose review at the online review aggregator website will be more influential on customer purchase intention of Indonesia’s moviegoers. Data of 220 Indonesia’s millennial generation were retrieved and analyzed during the research. This research finds out that customers in Indonesia can be influenced by score or rating that comes from online review aggregator, an equally good review from critics and customer can increase customer purchase intention and vice versa. Furthermore, customer’s score or rating is the one more influential by a small margin compared to the score from critics.